Measuring the effect of spell recurrence on poverty dynamics - José Maria Arranz; Olga Cantó (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
The analysis of poverty dynamics yields important insights about the expected effectiveness of alternative social policies on poverty reduction. This paper analyses the effect of spell recurrence on poverty dynamics taking into account multiple poverty and non-poverty spells. Using longitudinal data for Spain we obtain that the poverty exit and re-entry rates vary not only with personal or household characteristics but also with spell accumulation and with the duration of past spells. Results indicate that the effect of duration dependence is significant and turns out to be different by spell order. Our findings support progress towards incorporating full individual poverty trajectories more explicitly in estimating the likelihood of future poverty.
Keywords: C41; D31; I32; 330; poverty dynamics; multiple spells; recurrence